Translation of Hepatitis A Virus IRES Is Upregulated by a Hepatic Cell-Specific Factor - Sadahiro, Akitoshi; Fukao, Akira; Kosaka, Mio; Funakami, Yoshinori; Takizawa, Naoki; Takeuchi, Osamu; Duncan, Kent E.; Fujiwara, Toshinobu (Frontiers in Genetics, 2018)
Many viruses strongly prefer to infect certain cell types, a phenomenon known as “tropism”. Understanding tropism’s molecular basis is important for the design of vaccines and antiviral therapy. A common mechanism involves viral protein interactions with cell-specific surface receptors, but intracellular mechanisms involving translation have also been described. In this report, we focus on Hepatitis A Virus (HAV) tissue tropism from the standpoint of the translational machinery. HAV genomic RNA, like other positive stranded RNA viruses, is devoid of a cap structure and its translation is driven by highly structured RNA sequences termed internal ribosome entry sites (IRESs) in the 5' untranslated region (UTR). Unlike most viral IRESs, HAV IRES-mediated translation requires eIF4E and the 3' end of HAV RNA is polyadenylated. However, the molecular mechanism of HAV IRES-mediated translation initiation remains poorly understood. We analyzed HAV-IRES-mediated translation in a cell-free system derived from either non-hepatic cells (HeLa) or hepatoma cells (Huh7) that enables investigation of the contribution of the cap and the poly(A) tail. This revealed that HAV IRES-mediated translation activity in hepatoma cell extracts is higher as compared to extracts derived from a non-hepatic line. Our data suggest that HAV IRES-mediated translation is upregulated by a hepatic cell-specific activator in a poly(A) tail-independent manner.